Cryptococcus neoformans and PLWH: the role of serum cryptococcal antigen screening - Gül, Özlem; Duygu Demirbaş, Nazife; Barış, Ayşe; Derin, Okan; Tahtasakal, Ceren Atasoy; Öncül, Ahsen; Sevgi, Dilek Yıldız; Dökmetaş, İlyas (The Journal of Infection in Developing Countries, 2025)
Introduction: Serum cryptococcal antigen (CrAg) screening is crucial for early diagnosis of cryptococcal meningitis. This study presents the results of CrAg screening among people living with HIV (PLWH) followed in our clinic over the past six years. Methodology: Patients with a CD4+ T cell count below 200 cells/µL who were tested for CrAg were included in the study. Data regarding age, gender, comorbidities, CD4+ T cell count, HIV RNA level, blood culture results, and cerebrospinal fluid (CSF) findings—including CrAg, microscopy, culture, and PCR—were retrospectively collected. Descriptive statistical methods were used for the analysis. Results: Serum CrAg testing was performed on 99 patients, nine of whom tested positive. Among the patients with positive antigenemia, four were diagnosed with cryptococcal meningitis. In two cases, serum CrAg positivity was interpreted as false-positive due to the absence of clinical or laboratory findings consistent with cryptococcal infection. One patient died shortly after the CrAg test and could not be further evaluated. Two patients were lost to follow-up; however, one of them presented with symptoms two months later and was diagnosed with cryptococcal meningitis. Additionally, there was one patient with confirmed cryptococcal meningitis despite an initial negative serum CrAg result. Conclusions: CrAg positivity may be detected during the asymptomatic phase of cryptococcal infection. Although current guidelines recommend serum CrAg screening for individuals with CD4+ T cell counts below 100 cells/µL, the detection of positive results in those with CD4+ T cell counts above this threshold should also be carefully evaluated, considering the possibility of false-positive or false-negative results.